A Systematic Review of the Effects of Aerobic and Anaerobic Biofilter Processes on the Reduction of Biological Oxygen Demand (BOD) in Domestic Wastewater - Zairinayati; Aris Citra Wisuda; Norhashima Abd Rashid; Chun Hoe Tan (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Domestic wastewater significantly contributes to environmental degradation due to its elevated Biological Oxygen Demand (BOD), indicating the concentration of organic contaminants that deplete oxygen in aquatic ecosystems. Biofilter-based treatment technologies, both aerobic and anaerobic, have emerged as sustainable alternatives; nonetheless, their comparative efficacy remains inadequately investigated. Discussion: This systematic study, adhering to PRISMA principles, evaluates the efficacy of aerobic and anaerobic biofilters in diminishing BOD levels in home wastewater. A thorough literature search utilizing Publish or Perish software across five databases Scopus, DOAJ, ScienceDirect, PubMed, and Google Scholar was conducted to find pertinent articles published from 2019 to 2025. Of the 1210 articles initially discovered, ten satisfied the inclusion criteria according to the PICOS framework. Research indicates that both aerobic and anaerobic systems markedly decrease BOD values. Aerobic biofilters provide quick organic matter decomposition and superior removal efficiency, while anaerobic systems are beneficial for energy conservation and diminished sludge production. Numerous studies underscore the improved effectiveness of hybrid or sequential biofilter systems, demonstrating a synergistic impact when both approaches are utilized together. Conclusion: Both aerobic and anaerobic biofilters effectively reduce BOD levels in home wastewater. Hybrid systems offer a notably advantageous solution by amalgamating the qualities of both methods. Future study must concentrate on refining operational parameters and assessing the long-term scalability of integrated biofilter technology to enhance sustainable wastewater management.